Clarify Artificial Intelligence (AI) decisions models rights in Intelectual Property (IP) system - Aveni, Alessandro; Faria, Luísa Campos (Revista JRG de Estudos Acadêmicos, 2024)
The paper explores the relationships between Artificial Intelligence (AI) and Intellectual Property (IP) system of rights protection. The discussion clarify the characteristics of IP system, who is the registered owner, what is the registration object, and where the registration takes place. The research seeks WIPO's advice and the general trend of AI experts' discussions and tries to dig deep into definitions and meanings. The research also shows the mainstream explication why AIs not entitled as owner of an IP. In other case AI’s integrated into a process or a digital product a AI tool to solve a well-known problem, it is part of the organization's management and resources. Thus, innovation's certification belongs to the company or the public organization that sponsored it. The result of the research shows a summary framework of all the rights when used as a tool for decisions and risk of assuming AI as a system or as a model to support decisions specially for Public Administration.